The history of UiTM Sarawak / Enabella Tasha Dennis ... [et al.] - Dennis, Enabella Tasha; Juman, Juliet Cheria; Abdul Khalik, Khairunisa; Nyareng, Rasiba (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The UiTM Samarahan campus is the second branch campus of Universiti Teknologi MARA located in the state of Sarawak, Malaysia. This campus was established in Batu Lintang, Kuching around 1973-74. Now, the permanent campus of UiTM Sarawak is located in Kota Samarahan. This university is one of the first public universities built in the state of Sarawak.